EDUKASI TEKNIK STORYTELLING UNTUK GURU PAUD DALAM MENINGKATKAN KEMAMPUAN BAHASA INGGRIS ANAK USIA DINI - Sasmita, Ruwaiza; Marpaung, Tiara Azzahra; Majanto, Ajat; Zakiyah, Dika; Nur, Wahyuni Shofinna; Utami, Mutiara Widya (Andromeda: Jurnal Pengabdian Masyarakat Rafflesia, 2025)
This community service activity aims to provide education about storytelling techniques to PAUD (Early Childhood Education) teachers to improve English language skills in early childhood. Storytelling is an effective method in instilling character values, increasing creativity, and introducing English in a fun way from an early age. This activity was carried out at PAUD Islam Intan Insani, Bengkulu City, on November 23, 2024, involving 17 teachers.The method of implementing the activity consists of three main stages, namely training, practice with guidance, and monitoring and evaluation. In the training stage, the teachers were given materials on the basic concepts of storytelling, vocal techniques, the use of props, and the selection of suitable stories for children. Furthermore, in the practice stage, the participants practiced the techniques they had learned. The last stage, monitoring and evaluation, assessed the teachers' understanding and ability to apply the storytelling technique in the classroom.The results of this activity show that the teachers understand the  storytelling technique well and are able to apply it effectively in teaching and learning activities. This activity has a positive impact on improving the teachers' teaching skills and increasing children's enthusiasm for learning English through stories. Thus, this activity supports the creation of fun and meaningful learning from an early age. Keywords: storytelling; early childhood education; English language learning; teacher training; PAUD.